Photoreduction of Cr(VI) Ions in Aqueous Solutions by UV/TiO2 Photocatalytic Processes - Chih Ming Ma; Yung Shuen Shen; Po Hsiang Lin (International Journal of Photoenergy)
This study discussed the photoreduction of Cr(VI) ions in aqueous solutions by UV/TiO2 photocatalytic processes under various operational factors. Experimental results showed that the removal rate of Cr(VI) increased with decreasing solution pH values and with increasing dosages of organic compounds, indicating that the recombination rate of electrons and h+ can be retarded in the reaction systems by the addition of the scavenger, thus raising the reaction rate of Cr(VI). The relationship of the chemical reaction rate of Cr(VI), TiO2 dosage, and changes of Cr(VI) concentration was expressed by the pseudo-first-order kinetic equation. Comparing the experimental results of two different doping metals in modified TiO2 photoreduction systems, the removal rate of Cr(VI) by the Ag/TiO2 process is larger, possibly because the electron transferring ability of Ag is superior to that of Cu. However, the photoreduction rates of Cr(VI) by modified UV/TiO2 processes are worse than those by a nonmodified commercial UV/TiO2 process.